2009
DOI: 10.1089/ten.tec.2008.0518
|View full text |Cite
|
Sign up to set email alerts
|

Application of Platelet-Rich Plasma in Plastic Surgery: Clinical andIn VitroEvaluation

Abstract: The clinical use of platelet-rich plasma (PRP) for a wide variety of application has been reportedly employed most prevalently in problematic wounds, maxillofacial and hemi-facial atrophy, Romberg Syndrome, and diabetic foot ulcers. To our knowledge, PRP has never been described in the enhancement of fat grafting during tissue-engineering application in vivo. The authors describe the preparation of PRP and its use in a series of 43 patients who underwent plastic, reconstructive, and maxillofacial surgery for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
226
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(235 citation statements)
references
References 35 publications
3
226
1
3
Order By: Relevance
“…It is also used in orthopaedic and oral maxillofacial surgery where it accelerates autogenous bone graft healing (Fennis et al, 2004;Marx et al, 1998;Simon et al, 2009), and in cosmetic surgery (Man et al, 2001). PRP has also been used in combination with mesenchymal stem cells (MSC) to promote bone regeneration (Hibi et al, 2006;Ito et al, 2006;Kitoh et al, 2004;Kitoh et al, 2007;Lucarelli et al, 2003;Pieri et al, 2008) or mixed with fat cells for breast reconstruction, to correct painful, adherent scars, and to solve progressive hemifacial atrophy (Azzena et al, 2007;Cervelli et al, 2009a;Cervelli et al, 2009b;Cervelli et al, 2009c;Cervelli et al, 2009d;Fulton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used in orthopaedic and oral maxillofacial surgery where it accelerates autogenous bone graft healing (Fennis et al, 2004;Marx et al, 1998;Simon et al, 2009), and in cosmetic surgery (Man et al, 2001). PRP has also been used in combination with mesenchymal stem cells (MSC) to promote bone regeneration (Hibi et al, 2006;Ito et al, 2006;Kitoh et al, 2004;Kitoh et al, 2007;Lucarelli et al, 2003;Pieri et al, 2008) or mixed with fat cells for breast reconstruction, to correct painful, adherent scars, and to solve progressive hemifacial atrophy (Azzena et al, 2007;Cervelli et al, 2009a;Cervelli et al, 2009b;Cervelli et al, 2009c;Cervelli et al, 2009d;Fulton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Eppley et al reported that platelet-rich plasma growth factors stimulate endothelial cells near their application, favoring proliferation and formation of new capillaries [30]. Also, PRP enhances fat graft survival via proliferation of adipose stromal cells (ASCs) or stimulation of ASCs to differentiate into adipocytes [31]. In addition, Kakudo et al showed that activated platelet-rich plasma contains large amounts of PDGF-AB and TGF-β1 that promote the proliferation of human adipose-derived stem cells and human dermal fibroblast in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is thus used more and more often in the plastic, reconstructive and aesthetic surgery fields [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…These growth factors include platelet-derived growth factor (PDGF), insulin-like growth factor (IGF), and vascular endothelial growth factor (VEGF). Because of this, PRP is frequently used today in craniofacial, orthopedic, and neurological surgery [8][9][10][11] . PRP increases the success of grafting when fat grafts are applied in various regions of the body [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, PRP is frequently used today in craniofacial, orthopedic, and neurological surgery [8][9][10][11] . PRP increases the success of grafting when fat grafts are applied in various regions of the body [11][12][13][14] . Moreover, Erkilet et al [15] showed positive effects of PRP when used on its own on the tympanic membrane.…”
Section: Introductionmentioning
confidence: 99%